PERANCANGAN SISTEM INFORMASI PEMETAAN FASILITAS PELAYANAN KESEHATAN DI KOTA PONTIANAK BERBASIS WEB - Pratiwi, Amey Indah (Jurusan Informatika Universitas Tanjungpura, 2015)
Abstract - Problems that occured in the public related to the health care facilities at Pontianak City lead to the information about health care facilities makes public difficult to find information about doctor’s actual schedule and detail of the types of health services. Web-based Mapping Information System for Health Care Facilities at Pontianak City is a mapping information about distribution of the location of health care facilities and information about the types of health services. Because of the web-based Mapping Information System, it helped public to know the information faster and easier to find the health care facilities locations, the types of health services, doctor’s schedule and his status presence, the presence of the types of the health services and presence of service registration. The test result using questionnaire showed this web-based mapping information system can help the complaints of the health care facilities. The test result using Likert’s Summated Rating (LSR) got total score 1240 that showed the correspondent for this maping information system about health care facilities at Pontianak city was positive and successful.